Comparative performance of different varieties of large cardamom (Amomom subulatum Roxb.) under mid altitude of Amnachal Pradesh - Yadav, A K Dubey, D S (Journal of Spices and Aromatic Crops, 2001)
Studies were conducted to assess the performance of eight varieties of large cardamom at mid altitudes (660 meters MSL) in Arunachal Pradesh. Out of the eight varieties tested, Ramla,' Sawney, Madhusey and Ramsey performed better and can be introduced for commercial cultivation at mid altitude region of Arunachal Pradesh.